The Photoassociation Reaction of Ultracold Atoms (Journal of Atomic and Molecular Sciences, 2015)
Photoassociation reaction is the process in which two colliding atoms (or thecolliding atom-molecule system) absorb a photon to form an excited molecule. Sincethe researches based on the ultracold atomic and molecular systems have attractedgreat attention both from theorists and experimentalists, the ultracold photoassociationreaction is becoming an ascendant research field. In this paper, we review brieflythe investigation history of the photoassociation reaction for ultracold atoms, especiallythe basic theory of collision and the photoassociation in different light fields,and the research on the external-field manipulation of ultracold atoms collisions isalso prospected.
Keywords: ultracold atoms; photoassociation reaction; collision theory.